2021
DOI: 10.3390/agronomy11112233
|View full text |Cite
|
Sign up to set email alerts
|

Speciation of P in Solid Organic Fertilisers from Digestate and Biowaste

Abstract: Phosphorus (P) is a finite resource and its reuse in organic fertilisers made from biowaste and manure should therefore be encouraged. The composition of solid organic fertilisers (SOFs) depends on the type of feedstock and processing conditions, and this may affect P speciation and hence P availability. Phosphorus speciation was assessed in eighteen different SOFs produced from biowaste and digestate. Available P was determined in 10 mM CaCl2 extracts at a fixed pH of 5.5 and at a fixed total P concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 61 publications
4
11
1
Order By: Relevance
“…Elevated OM contents in the SFs of digestate make them better suited as organic soil improvers (Egene et al, 2020;Peters and Jensen, 2011) with the potential to increase C sequestration in soils (Veeken et al, 2017). Drying of the SF of digestate (as in SFD-AmP and SFD-WNE), concentrates the N (24 and 31 g kg − 1 , respectively), making them also applicable as N or P fertilisers (Regelink et al, 2021). On the other hand, ammonia stripping of the LF of digestate produces pure mineral N fertilisersas in AW-WNE, AS-A&S and AS-BNS with total N contents of 53, 76, and 41 g kg − 1 , respectively.…”
Section: Physicochemical Properties Of the Biobased Fertilisersmentioning
confidence: 99%
“…Elevated OM contents in the SFs of digestate make them better suited as organic soil improvers (Egene et al, 2020;Peters and Jensen, 2011) with the potential to increase C sequestration in soils (Veeken et al, 2017). Drying of the SF of digestate (as in SFD-AmP and SFD-WNE), concentrates the N (24 and 31 g kg − 1 , respectively), making them also applicable as N or P fertilisers (Regelink et al, 2021). On the other hand, ammonia stripping of the LF of digestate produces pure mineral N fertilisersas in AW-WNE, AS-A&S and AS-BNS with total N contents of 53, 76, and 41 g kg − 1 , respectively.…”
Section: Physicochemical Properties Of the Biobased Fertilisersmentioning
confidence: 99%
“…Considering the limited worldwide range of phosphorus (P) reserves [1][2][3][4], which as phosphorites were included in the Critical Raw Materials List by the European Commission in 2014 [1,2], the problem of finding new P sources for agricultural soils has become a challenge for modern generations. Hence, reducing the use of mineral fertilisers and making greater utilisation of renewable P sources has become an emerging direction for agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…The fundamental issue, from an agronomic point of view, is the soil available P dynamics, which depend on many factors, most often related to the effect of pH, clay content, and the elemental composition of Al, Fe, or Ca in soil solution. The role of organic matter is also important with respect to P availability, however, we often encounter ambiguous and even contradictory findings in the literature regarding its effect on P sorption, and therefore also on P (bio)availability [3,[21][22][23][24]. Several studies have shown that organic matter introduced with organic amendments reduced P fixation and enhanced P uptake in soils [21].…”
Section: Introductionmentioning
confidence: 99%
“…Research on the different types of natural and exogenous organic matter (OM) and their fractions and effects on phosphorus (P) retention in soil has become a consistent element within issues of global concern [1][2][3][4][5][6][7][8][9]. The progressive degradation of arable soils, i.e., drought, contamination, soil organic matter losses or the scarcity of plant nutrients (in particular P)-has stimulated strategies to utilize infertile and even degraded soils.…”
Section: Introductionmentioning
confidence: 99%